Gossip and the efficiency of interactions - Dietmar Fehr; Matthias Sutter (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2016)
Human communication in organizations often involves a large amount of gossiping about others. Here we study in an experiment whether gossip affects the efficiency of human interactions. We let subjects play a trust game. Third parties observe a trustee's behavior and can gossip about it by sending a message to the trustor with whom the observed trustee will be paired (for the first time) in the next round. While messages are non-verifiable and sometimes also incorrect, the possibility of gossip is highly efficiency-increasing compared to a situation without any gossip. In two further control treatments, we show that the mere fact of being observed by third parties cannot explain the efficiency-increasing effect of gossip, and that noisy gossip (where information transmission from third parties to trustors can fail) still increases efficiency, but less so than if information transmission is undisturbed.
Keywords: C72; C92; 330; gossip; communication; trust game; efficiency